Honor killing and the cycle of social influence: A study of the Pakistani bride through Albert Bandura’s social learning theory - Asif, Muhammad; Lahiani , Hanene; Alhourani , Mohammad I.; Al-Mahamed, Ahmad M.; Abou Adel, Mohamad (Research Journal in Advanced Humanities, 2025)
This research employs Albert Bandura's Social Learning Theory to analyze honor-related violence as presented by Bapsi Sidhwa in her novel The Pakistani Bride. Honor killings are often committed and justified under the guise of preserving the family's honor. This study aims to explore how such violence is modeled, reinforced, and sustained through social observation, cultural norms, and intergenerational transmission. The application of Social Learning Theory demonstrates that honor related violence is not genetically transferred, but it is learned and reinforced by societal rewards and punishments. The novel portrays male, well-known figures who engage in violent behavior as role models for future generations, while women are subjected to subservience as a result of cultural norms. This research also clarifies the phenomenon of legitimization of the honor-based violence by vicarious reinforcement and fear of ostracism in the society. The findings underline the need for cultural and educational programs to question these negative social conventions. By adding to the larger conversation on gender-based violence and the underlying systems that support it, The Pakistani Bride helps to advocate a radical change in societal views of honor and gender roles.